The Struggle Against Global Warming: The Prospects for Renewable Energy Sources in Russia - Georgy Safonov (Foresight and STI Governance)
Russia can and must take a leading position in promoting renewable energy. The widespread use of renewable energy sources will contribute to economic growth; improve living standards and quality of the environment. Simultaneously, Russia go the way of prevention of irreversible changes in the global climate system.